Selecting alternative sterile and non-sterile substrates for mycorrhizal inoculant production - Mathias Barroso, Laura; Dias da Silva Lisboa, Roberta; da Silveira, Silvaldo Felipe; Silva Samarão, Solange; Aparecida Rodrigues, Luciana (Revista Ceres, 2022)
Alternative substrates were evaluated for mycorrhizal inoculants production considering the beneficial effects of arbuscular mycorrhizal fungi (AMF) for plants and environment. The first step of the experiment aimed at evaluating the potential of substrates produced from sugarcane bagasse (SB), coconut fibre (CF) and urban waste compost (UWC) to produce AMF inoculants, by using Brachiaria decumbens as multiplier plant. The experiment has followed a randomized block design, at 7x3 factorial arrangement (seven substrates: SB, CF, SB+CF 1:1, SB+UWC 3:1, CF+UWC 3:1, SB+CF+UWC 3:3:2, Soil+Sand 3:1, vs. three substrate preparations: inoculated/sterilized, inoculated/non-sterilized, non-inoculated/sterilized). Inoculums produced in the first experimental stage were tested at the second stage, based on the inoculated/sterilized preparation. Seed germination, dry shoot biomass, mycorrhizal root rate and total spore production were assessed in both tests. There was significant decrease in seed emergence in organic substrates in relation to Soil+Sand, although the plants growth in organic substrates was greater. Artificial inoculation was not superior to spontaneous substrate mycorrhization or affected inoculum production. Mycorrhizal colonization of roots was equivalent in most organic substrates and in Soil+Sand. However, spore production stood out in organic substrate mixes, mainly when CF and UWC were used. This finding was confirmed at the second experimental stage.